Speech therapy students’ perceptions from a private University on the occurrence of university violence (Research, Society and Development, 2023)
Objective: To investigate the perception of graduates of a Speech Therapy course at a private University in the State of São Paulo regarding the occurrence of university violence. Methodology: 51 students participated and responded to a structured and validated scale with 22 statements about different situations of violence in the university environment with a 4-point Likert Scale (1 – never; 2 – rarely; 3 – sometimes; and 4 – always). The results were analyzed, adopting simple frequency measures (simple percentage) to identify the response categories. Results: Different types of violence were identified in the student-student and student-teacher relationships, mainly involving issues of machismo and academic performance. Conclusion: Based on the students' perceptions, it was possible to observe that the participants recognize the presence of violence in the university environment. This study can support the local diagnosis of situations like these and direct the foundation of prevention measures and guidance on this topic.